Hubungan burnout dengan kepuasan kerja dalam kalangan guru tingkatan enam di daerah Meradong, Sarawak - Law, Cheng Sin (2011)
The purpose of this study was to explore to what extent the level of burnout and job satisfaction among teachers in the district of Sixth Form Meradong. This study also examined the relationship between job satisfaction and burnout. A total of 75 respondents were randomly selected from grade six teachers of three secondary schools in the district Meradong, Sarawak in the study. All information obtained by using a questionnaire. Data collected were processed by using Statistical Packages for Social Sciences' (SPSS version 12). Statistical techniques used are the percentages, cross tabulation and Pearson to find answers to research questions formed. The findings showed that respondents have experienced low level burnout and job satisfaction. Overall analysis of differences in demographic inference showed no significant difference between demographic characteristics of burnout and job satisfaction. However, the factors of burnout and job satisfaction are important to every individual who worked as teachers who are satisfied with his/her work will become more productive and provide greater commitment to their jobs